Analytical solution of non-linear partial differential equation by using the extended (𝐆′/𝐆) expansion method with non-linear auxiliary equation - Karmaker, Bishwajit (BRAC Univeristy, 2018)
This thesis is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Science in Mathematics 2018.